A new perspective on referentiality in elicited narratives: Introduction to the Special Issue. Issue 2 (April 2022) - Gagarina, Natalia; Bohnacker, Ute
This special issue investigates the use of referential expressions in elicited picture-based narratives by children with and without developmental language disorders, across a range of languages and language combinations. All contributions use the Multilingual Assessment Instrument for Narratives (MAIN, Gagarina et al. 2012, 2019). The studies featured in this issue cover monolingual and bilingual children aged 4–11 years, but focus mainly on age 4–7, a period in a child's life where great strides are made in the development of narrative skills. This collection of papers offers a new perspective on referentiality for several reasons: all studies use the same stimuli and by and large the same procedure for the elicitation of narratives. The stimuli, four picture-based stories, are controlled for comparability of protagonists, plot and story structure. They were designed as a 'visual' representation of a multidimensional model of story grammar. This methodological and theoretical base allows for a comparative investigation of referentiality (including reference introduction, maintenance and reintroduction) in narratives, across languages and populations. This introduction addresses theoretical aspects of referentiality in decontextualised discourse and reviews the literature regarding the impact of language-specific referential systems and the age and path of acquisition in typically developing children and children with developmental language disorders. We also discuss methodological aspects of eliciting referentiality in narratives in detail. This introduction thus seeks explanations for the diverse and sometimes contradictory empirical results regarding children's mastery of referentiality. Finally, an overview of the contributions in the special issue is given.